Shelf acetabuloplasty is associated with longer survival of the total hip arthroplasty in patients with late-detected hip dislocation: a cohort study of 70 hips with a modified Spitzy shelf procedure - Terje Terjesen; Stefan Huhnstock (Acta Orthopaedica, 2025)
Background and purpose: Our aim was to compare age at time of total hip arthroplasty (THA) and the THA survival time in patients with late-detected developmental dislocation and dysplasia of the hip (DDH) treated with traction in childhood who had either undergone acetabular shelf operation due to persistent DDH, or no previous acetabular surgery but persistent DDH, or no previous acetabular surgery and CE angle ≥ 18°. Methods: 112 patients (97 females; 144 hips) with late-detected DDH who had undergone THA were studied. 70 hips had undergone a modified Spitzy procedure (SA group) at the age of 8–33 years. They were compared with 2 groups that had not undergone previous pelvic surgery: a “Dysplasia” group with residual (persistent) acetabular dysplasia (CE angle < 18°, 33 hips) and a “Normal” group with no residual dysplasia (37 hips). We analyzed age at THA and the survival rate (percentage of THAs not having undergone revision). Results: Mean patient age at THA did not differ between the SA group (52 years) and the Dysplasia group (49 years; P = 0.1). 11 THAs had been revised in the SA group and 9 in the Dysplasia group. Kaplan–Meier analysis showed 20-year survival rates of 88% in the SA group and 68% in the Dysplasia group. The estimated survival time of THA was significantly higher in the SA group than in the Dysplasia group (29.4 and 19.8 years; P = 0.01). Mean age at THA was significantly lower in the Dysplasia group than in the Normal group (49 and 55 years), but there was no significant difference between these groups in estimated survival time of THA. Conclusion: A previous acetabular shelf operation in patients with persistent DDH does not appear to delay age at THA but THA had better survival rate.